Popular sovereignty and interests as seen by the precursors of public opinion theory - Lang, Kurt (Javnost (Ljubljana), 2003)
Classical writers, going back as far as John Locke, recognized public opinion as a powerful force. That the passions and interests of real people often divert them from pursuing the common good confronted them with a dilemma: what is desired by all is not necessarily what reason shows to be in their general interest. The dilemma points to the necessity of government and also of institutional arrangements to mediate between the people and the makers of laws binding on everyone. The paper examines in particular the views of Rousseau on assemblies, of Hegel on the development of universal norms, and of von Stein on social movement. It concludes that public opinion exists only in the form of discourse and that it exerts influence either when some part acts as a concrete group or when the preferences of an abstract aggregate of individuals converge on a particular party, candidate, or legislative proposal.
Keywords: družbeno vedenje; suverenost; interesi; javno mnenje; zgodovinski pregledi